Effect of agmatine on brain L-citrulline production during morphine withdrawal in rats: A microdialysis study in nucleus accumbens - ARICIOĞLU, FEYZA; YANANLI, HASAN RACİ (ELSEVIER SCIENCE BV, 2007)
Agmatine, an endogenous nitric oxide (NO) synthase inhibitor and ligand for imidazoline receptors, has been previously shown to prevent morphine dependence in rats. The present study was designed to investigate No formation in nucleus accumbens core region (NAcc) during naloxone (NL)-precipitated morphine withdrawal in rats treated with agmatine or L-NAME by using intracerebral microdialysis in freely moving rats, through measuring extracellular L-citrulline concentrations, an indirect sign of NO production since equal amounts Of L-citrulline and NO are produced from L-arginine. L-Citrulline levels in the NAcc core did not change following administration of agmatine (40 mg/kg i.p.) or L-NAME (100 mg/kg i.p.) in control rats. Both agmatine and L-NAME attenuated withdrawal symptoms of morphine in NL (2 mg/kg i.p.) -precipitated withdrawal. L-Citrulline levels showing the release of NO increased in morphine-dependent rats during NL-precipitated withdrawal. Agmatine and L-NAME treatments significantly suppressed the increase in L-citrulline levels compared to physiological saline-treated rats in this setting. The results suggest that the release Of L-citrulline in NAcc may be involved in the processes of morphine withdrawal and agmatine as an endogenous inhibitor of NO synthase may be one of the factors involved in the changes in the physiology and behavioral state during opioid withdrawal and may have pharmacological importance. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: agmatine; morphine withdrawal; NO (nitric oxide); microdialysis; L-NAME; nucleus accumbens; NITRIC-OXIDE SYNTHASE; CLONIDINE-DISPLACING SUBSTANCE; PHYSICAL-DEPENDENCE; RECEPTOR ANTAGONISTS; OPIOID WITHDRAWAL; IN-VIVO; INHIBITION; NALOXONE; TOLERANCE; ALPHA(2)-ADRENOCEPTOR